Knowing more from less: how the information environment increases knowledge of party positions - Susan Banducci; Heiko Giebler; Sylvia Kritzinger (British journal of political science, 2017)
Access to information is a hallmark of democracy, and democracy demands an informed citizenry. Knowledge of party positions is necessary for voters so that electoral choices reflect preferences, allowing voters to hold elected officials accountable for policy performance. Whereas most vote choice models assume that parties perfectly transmit positions, citizens in fact obtain political information via the news media, and this news coverage can be biased in terms of salience – which leads to asymmetric information. This study examines how information asymmetries in news coverage of parties influence knowledge about political party positions. It finds that the availability of information in the news media about a party increases knowledge about its position, and that party information in non-quality news reduces the knowledge gap more than information in quality news.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.; http://dx.doi.org/10.7910/DVN/SBGZOJ
Keywords: 330; Information; Medien; Berichterstattung; Wissen; Parteipolitik; Partei; politischer Einfluss